Effect of Virtual Education on Academic Performance Generated by COVID-19 - Rubio-Rodríguez , Gustavo Adolfo; Flórez Guzmán , Mario Heimer; Palma-Cardoso, Elizabeth; Vanegas Zamora , Rubell Juneidy; Manjarrés Hincapié, Juan Gabriel; Reinoso Córdoba , Alejandro (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The aim of this research is to analyze the impact of implementing virtual education on the academic performance of primary and secondary school students in a private school in Ibagué, Colombia, during the COVID-19 pandemic crisis. The survey was administered to 183 parents and nine teachers at the school as a data collection technique for the study. The research results revealed that the school maintained its quality in conducting virtual classes at the elementary and high school levels. Similarly, the students’ performance was maintained compared to the previous year of the pandemic. As a conclusion, it has been determined that the school directors’ implementation of the virtual education model and the capabilities of the teaching staff were successful in maintaining the quality of education during the pandemic.